2008
DOI: 10.1002/path.2438
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐1 receptor acts as a growth regulator in synovial sarcoma

Abstract: Synovial sarcomas account for 5-10% of all soft tissue sarcomas and the majority of synovial sarcomas display characteristic t(X;18) translocations that result in enhanced transcription of the insulin-like growth factor-2 (IGF-2) gene. IGF-2 is an essential fetal mitogen involved in the pathogenesis of different tumours, leading to cellular proliferation and inhibition of apoptosis. Here we asked whether activation of IGF signalling is of functional importance in synovial sarcomas. We screened human synovial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 29 publications
(33 reference statements)
2
47
0
Order By: Relevance
“…26 In brief, fibroblasts were seeded using DMEM supplemented with 10% FBS followed by a 48 h interval of low serum conditions. Subsequently, TGF-b1 ligand (2 ng/ml) was added to fibroblast culture for 72 h. In all, 100 000 cells in medium containing 0.5% FBS were added into the upper chambers of transwells of 6.5 mm diameter and 8.0 mm pore size (Corning Costar Corporation, Bodenheim, Germany).…”
Section: Transwell Motility Assaymentioning
confidence: 99%
“…26 In brief, fibroblasts were seeded using DMEM supplemented with 10% FBS followed by a 48 h interval of low serum conditions. Subsequently, TGF-b1 ligand (2 ng/ml) was added to fibroblast culture for 72 h. In all, 100 000 cells in medium containing 0.5% FBS were added into the upper chambers of transwells of 6.5 mm diameter and 8.0 mm pore size (Corning Costar Corporation, Bodenheim, Germany).…”
Section: Transwell Motility Assaymentioning
confidence: 99%
“…This could In synovial sarcoma, in vitro studies have found that the SS18-SSX oncogene induces IGF2 expression which seems critical to convey tumorigenic properties. [48][49][50] IGF2 expression was associated with both the ÀSSX1 and ÀSSX2 translocation subtypes. 48 In this study, we present evidence that in primary synovial sarcoma tumor specimens, IGF2 is highly expressed at the protein level, supporting translational relevance to patients of these experimental findings, and attempts to target this pathway in patients using IGF signaling inhibitors.…”
Section: Discussionmentioning
confidence: 98%
“…78 Preclinical studies are ongoing, but its antitumour activity has been demonstrated in musculoskeletal tumours, 79 hepatocellular carcinoma, 80 NET, 76 malignant mesothelioma, 81 HNSCC, 77 colorectal cancer, 82 neuroblastoma, 83 Ewing's sarcoma, 84 multiple myeloma, 85 pancreatic cancer, 86 gastrointestinal stromal tumour, 87 gastrointestinal cancer, 88 breast cancer 89 and synovial sarcoma. 65 As expected for a specific IGF1R kinase inhibitor, NVP-AEW541 abrogated IGF1-mediated survival, inhibited the proliferation of cultured tumour cell lines by inducing apoptosis and cell cycle arrest in vitro, and significantly inhibited the growth of tumour xenografts in vivo. 65,76,77,[79][80][81][82][83][84][85][86][87][88][89] Accumulating evidence suggests that NVP-AEW541 represents a potential therapeutic strategy for the treatment of tumour types in which IGF1R-mediated signalling is required for driving/ survival.…”
Section: Nvp-aew541mentioning
confidence: 99%
“…Treatment of synovial sarcoma cell lines with the IGF1R antagonist NVP-AEW541 led to increased apoptosis, and impaired growth, mitotic activity and cell migration. 65 IGF1R did not enhance motility in LCC6-DN cells (a breast cancer cell line with dominant negative IGF1R), in contrast to increased motility in wild-type LCC6 cells, suggesting that metastasis is inhibited by truncated IGF1R. 66 The injection of mice with LCC6, but not LCC6-DN, cells resulted in the formation of lung metastases, indicating that IGF1R regulates metastasis independently from tumour growth.…”
Section: Igf-ir Signalling In Malignancymentioning
confidence: 99%